Neuropsychological Impairment, Brain Injury Symptoms, and Health-Related Quality of Life After Pediatric TBI in Oslo - Holthe, Ingvil Laberg; Dahl, Hilde Margrete; Rohrer-Baumgartner, Nina; Eichler, Sandra; Elseth, Marthe Fjellheim; Holthe, Øyvor; Berntsen, Torhild; Yeates, Keith Owen; Andelic, Nada; Løvstad, Marianne (Frontiers in Neurology, 2022)
Descriptions of clinical outcomes in pediatric traumatic brain injury (pTBI) in Scandinavia are sparse. The Oslo site of the European CENTER-TBI study has performed a pTBI outcome study in a hospitalized population. The main objective was to investigate neuropsychological outcomes, self- and parent reported symptoms associated with brain injury, and quality of life in children aged 1-15 years, 5-8 months after injury. Fifty-two children were included, and 45 completed the assessments. The sample consisted of 15.4% severe, 21.2% moderate, and 63.4% mild TBI. Subjectively experienced problems with concentration and fatigue were reported by the parents of nearly half of the children. Higher brain injury symptom load was associated with lower quality of life, but was unrelated to injury severity. Group average scores of the sample on neuropsychological testing appeared unimpaired relative to normative means aside from lower performance in working memory. However, based on an impairment index (i.e. 2 or more tests being >1.5 SD below normative mean), the presence of weak cognitive performance was evident in as many as 45.4 % of the sample. Two thirds of the sample also showed abnormally large intraindividual variability in cognitive functioning (i.e. significant WISC-IV index discrepancies). The findings highlight the need to look beyond group averages on neuropsychological testing. Utilizing an impairment index and considering intraindividual performance variability conveyed deficits that may warrant clinical follow-up. The association of brain injury symptoms with quality of life but not injury severity emphasizes the need to consider symptoms after TBI within a biopsychosocial framework.